Social Intelligence and Academic Procrastination of Prospective Biology Teacher Students at FKIP Riau University - Fadhilah, Amaliya Nurul; Firdaus, Firdaus; Putra, Riki Apriyandi (Journal of Educational Sciences, 2024)
Academic procrastination is an act of delaying, postponing the completion of assignments. Procrastination is an irresponsible act. Meanwhile, a responsible attitude is included in social competence. Social competence can be possessed if individuals have good social intelligence. Social intelligence is an individual's ability to interact harmoniously with their environment and be able to receive and process existing information to find solutions to existing problems. The aim of this research is to determine the relationship between social intelligence and academic procrastination of Biology teacher candidates at FKIP Riau University. This research uses quantitative data and a survey with a sample of Biology teacher candidates at FKIP Riau University. The research results obtained a correlation value (r) of -0.242, namely that there is a low relationship between social intelligence and academic procrastination for Biology teacher candidates at FKIP Riau University. Negative correlation shows that the higher social intelligence, the lower procrastination. So it can be concluded that there is a relationship between social intelligence and academic procrastination of prospective biology teacher students at FKIP Riau University.